PVA and PMMA nano-composites: a review on strategies, applications and future prospects - Kalyani Palanichamy; Muthupandeeswari Anandan; Jayavel Sridhar; Varagunapandiyan Natarajan; Aravind Dhandapani (Materials Research Express, 2023)
Nanotechnology has facilitated unique ways of developing novel nano-composites. In that sense, polymer-based nano-composites are being extensively researched for their outstanding properties as a result of incorporating nano-fillers in the polymer matrix. They have activated enormous research interests owing to their potential in addressing environmental issues, packaging, optics, electronics, battery electrolytes, pneumatic actuation, molecular separations, sensors, biomedical applications, etc Hence, the authors intend to consolidate reported information about these polymer matrices, diverse inorganic nanofillers, and nano-filled polymer composites for improvement in properties and future advanced applications. The review exhaustively covers 15 years of literature on theoretical, experimental, and application aspects of PVA & PMMA-based nano-composites, mainly focusing on inorganic oxide-based fillers. It also summarizes the structure-property correlations that govern their performance. Hence this review is hoped to provide the readers with stimulating insights on strategies, noteworthy challenges, and future opportunities/prospects in developing polymer nano-composites that may cater to the need of our society and scientific industries as well.